Antibacterial, antibiotic-potentiating, and antiviral activities of selected endemic primary rainforest plants of Peninsular Malaysia - Masyitah Zulkipli; Mazdida Sulaiman; Layane Elbehairy; Khoo, Teng Jin; Nor Hayati Abdullah; Chandramathi Samudi Raju; Gheetanjali Kathirvalu; Veeranoot Nissapatorn; Nor Azizun Rusdi; Fiffy Hanisdah Saikim; Vladimir Zarubaev; John Kenny Rafon; et al. (Bentham Science Publishers, 2025)
Background: There is a need to identify original molecules to develop drugs for the treatment of microbial infections. Such chemical entities could be found in secondary metabolites of rainforest plants that are not so well-known. This study examines the antibacterial and antibiotic- potentiating effects, and antiviral activities of six rainforest plants endemic to the primary rainforest of Malaysia. Methods: Leaves, bark, fruits, and wood of Burkillanthus malaccensis, Cleistanthus bracteosus, Diospyros hasseltii, Kibatalia maingayi, Knema retusa, and Litsea spathacea were extracted successively with hexane, chloroform, and methanol, and tested against six human pathogenic bacteria species by disc diffusion and broth microdilution. The extracts were tested against influenza virus A/Puerto Rico/8/34 (H1N1) using MDCK cells. Results: Of the 42 extracts tested, the hexane extract of fruits of D. hasseltii inhibited the growth of E. coli with the MIC value of 39 μg/mL. The chloroform extract of leaves of C. bracetosus potentiated the activity of levofloxacin against P. aeruginosa. The strongest antiviral activity was observed with the chloroform extract of leaves of C. bracteosus with the IC50 value of 6.3 μg/mL. The chloroform extract of bark of B. malaccensis with the IC50 value of 0.6 μg/mL was the most cytotoxic. Conclusion: Preserving the primary rainforest of Malaysia is a means to preserve natural products with the ability to be developed as antimicrobial leads. In particular, D. hasseltii, C. bracteosus, and B. malaccensis could be examined for their active antimicrobial constituents.